Building the Character of a Just Generation: The Role of Hadith in Creating a Just and Harmonious Society - Tri Widya Oktaviani; Endad Musaddad (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
This article explores the essential role of hadith in shaping a just and moral generation amidst modern-day challenges. Using a qualitative approach through literature studies, this research examines how the values of justice found in the Qur'an and hadith can be applied in daily life, particularly through the vital role of parents in character education. Hadith is viewed not only as a source of Islamic law but also as a moral and ethical guide that fosters a fair and harmonious society. The findings highlight that instilling the value of justice from an early age through parental example and hadith-based education is a key strategy in building a knowledgeable, faithful, and noble generation.